A polynomial approach to robust channel estimator design for DS-CDMA systems - Cao, Chengtao (2008)
This thesis presents a series of research results on channel estimation problem for a DS-CDMA system in multipath fading channel environments. The focus of the thesis is a polynomial approach to robust estimation problems for uncertain channels with deterministic or stochastic parameter uncertainties under the MMSE or H infinity sense. The polynomial approach has the distinct advantage of lower computational complexity.